HUBUNGAN DIABETES MELITUS DENGAN KOLELITIASIS: TINJAUAN LITERARUR BERDASARKAN JUMLAH DAN UKURAN BATU - Birman, Yuliza; Bahri, Ahmad Fajar; Bahri, Rosmaini (Yayasan Nusantara Hasana Berdikari, 2025)
Diabetes mellitus (DM) and cholelithiasis are two conditions with increasing global prevalence. Several studies have indicated a significant association between DM and both the incidence and severity of cholelithiasis, particularly in relation to the number and size of gallstones. Objective: This article aims to review the literature regarding the pathophysiological mechanisms, epidemiological evidence, and morphological characteristics of gallstones in patients with diabetes mellitus. Methods: A literature search was conducted using electronic databases (PubMed, Google Scholar, ScienceDirect) for articles published within the last 10 years, using keywords such as “diabetes mellitus,” “cholelithiasis,” “gallstone size,” and “gallstone number.” Results: DM contributes to gallstone formation through impaired gallbladder motility due to autonomic neuropathy, bile supersaturation from dyslipidemia, and increased mucin expression that enhances cholesterol crystal nucleation. Patients with DM tend to develop multiple and/or larger gallstones, which are closely associated with a higher risk of complications such as cholecystitis and pancreatitis. Conclusion: Diabetes mellitus is strongly associated with an increased incidence and severity of cholelithiasis. Routine gallbladder screening is recommended for diabetic patients, particularly those with poor glycemic control, to prevent serious hepatobiliary complications.